2021
DOI: 10.1155/2021/7178253
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Astragalus Polysaccharide on Sepsis-Induced Acute Kidney Injury

Abstract: Objective. To explore the protective roles of Astragalus polysaccharide (APS) on acute renal injury (AKI) induced by sepsis. Methods. Firstly, an animal model of sepsis-induced AKI was established by injecting lipopolysaccharide (LPS) into mice. The mice were pretreated with an intraperitoneal injection of 1, 3, and 5 mg/(kg·d) APS for 3 consecutive days. The severity of kidney injury was then scored by histopathological analysis, and the concentrations of serum urea nitrogen (BUN) and serum creatinine (SCr) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Recently, Echinacea polysaccharide have been demonstrated to decrease ROS, malondialdehyde, and oxidized glutathione levels as well as increase SOD, CAT, and glutathione reductase while decreasing glutathione activity [32]. Astragalus polysaccharide could have increased T-SOD and GSH-Px activities as well as inhibited oxidative stress marker 3-NT expression in cisplatin-induced AKI mice [33]. Our results are consistent with these studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, Echinacea polysaccharide have been demonstrated to decrease ROS, malondialdehyde, and oxidized glutathione levels as well as increase SOD, CAT, and glutathione reductase while decreasing glutathione activity [32]. Astragalus polysaccharide could have increased T-SOD and GSH-Px activities as well as inhibited oxidative stress marker 3-NT expression in cisplatin-induced AKI mice [33]. Our results are consistent with these studies.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have also found that natural polysaccharides can improve numerous types of kidney diseases, including diabetic nephropathy [26,27], drug-related kidney injury [28,29], and renal ischemia-reperfusion injury [30]. Polysaccharides from Sanguisorba officinalis [31], Lycium barbarum [23], Echinacea [32], and Astragalus [33] have been reported to alleviate sepsis AKI via the suppression of oxidative stress and inflammatory responses. It has been demonstrated that C. cicadae and its extracts exert a protective role in kidney diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of free sICAM-1 to LFA-1 can promote the killing process involving CTL and NK cells, enhance the immune response of helper T cells, and involve in antibody-dependent cell-mediated cytotoxicity (ADCC) ( Gross et al, 2010 ). Sun et al (2021) showed that APS inhibited the expression of TNF-α, IL-1 β, IL-6, and IL-8 in a concentration-dependent manner to reverse sepsis-induced acute kidney injury in mice. Dong et al (2019b ) demonstrated that APS reduced the mRNA expression levels of TNF-α, IL-1 β, IL-6, and IL-17 in diarrheic mice.…”
Section: Discussionmentioning
confidence: 99%
“…HK-2 cells and iBMDMs were cultivated in DMEM (Gibco) basic medium supplemented with 5% fetal bovine serum and 100 U/ml penicillin-100 μg/ml streptomycin antibiotics at 37 °C under a 5% CO 2 -humidified environment. For the in vitro study, HK-2 cells were pretreated with APS (100 μg/ml) or an inhibitor of TGF-β (disitertide, P144, 100 μg/ml) for 3 h and then treated with saline or Ang II (100 nM) for 24 h (Sun et al, 2021;Jun et al, 2019).…”
Section: Cells and Treatmentmentioning
confidence: 99%
“…Astragalus polysaccharides are the main bioactive components extracted from Astragalus membranaceus. Astragalus polysaccharide extract (APS) is famous for its various pharmacological activities (Yang et al, 2019;Sun et al, 2021). APS is a critical active ingredient responsible for various bioactivities of Astragalus membranaceus.…”
Section: Introductionmentioning
confidence: 99%